Polymer Film Supported Bimetallic Au–Ag Catalysts for Electrocatalytic Oxidation of Ammonia Borane in Alkaline Media - Karabiberog˘lu, S¸u¨kriye Ulubay; Koc¸ak, C¸ ag˘rı Ceylan; Koc¸ak, Su¨leyman; Dursun, Zekerya (Nano-Micro Letters, 2016)
Ammonia borane is widely used in most areas including fuel cell applications. The present paper describes electrochemical behavior of ammonia borane in alkaline media on the poly(p-aminophenol) film modified with Au and Ag bimetallic nanoparticles. The glassy carbon electrode was firstly covered with polymeric film electrochemically and then, Au, Ag, and Au–Ag nanoparticles were deposited on the polymeric film, respectively. The surface morphology and chemical composition of these electrodes were examined by scanning electron microscopy, transmission electron microscopy, electrochemical impedance spectroscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. It was found that alloyed Au–Ag bimetallic nanoparticles are formed. Electrochemical measurements indicate that the developed electrode modified by Au–Ag bimetallic nanoparticles exhibit the highest electrocatalytic activity for ammonia borane oxidation in alkaline media. The rotating disk electrode voltammetry demonstrates that the developed electrode can catalyze almost six-electron oxidation pathway of ammonia borane. Our results may be attractive for anode materials of ammonia borane fuel cells under alkaline conditions.